Factors associated with mortality, amputation, pneumonia, and skin graft loss among electrical burn patients admitted in a Philippine tertiary hospital burn center from 2013 to 2019 - Mar Aristeo G. Poncio; Jose Joven V. Cruz (Elsevier, 2021)
Electrical burns are considered as the most devastating and one of the most common causes of burn admissions worldwide. It is cited as the 4th most frequent cause of admission among burn units worldwide. Approximately 1-20% of admission in the Philippine General Hospital Alfredo T. Ramirez Burn center is secondary to electrical burn. This is an analytic retrospective cohort study identifying factors associated with mortality, pneumonia, skin graft loss, and amputation among electrical burn patients admitted to the PGH ATR Burn Center from January 2013 to December 2019. Survival analysis was performed using Log Rank test and Cox proportional hazard regression model. Data analysis was performed using STATA 14. In this study, significant predictors of amputation identified are the following: compartment syndrome, fasciotomy, number of operations, and involvement of trunk and perineum. Significant predictors of mortality include use of metal rod, compartment syndrome, fasciotomy, total body surface area (TBSA), number of operations and age. The use of metal rod pertains to a patient holding a metal conductor near the power line. Significant predictors of pneumonia include the use of metal rod, time of injury, compartment syndrome, fasciotomy, TBSA, number of operations and time of injury to admission/referral and age. Compartment syndrome secondary to high voltage electrical burn injury is strongly associated with amputation by as much 2.13 fold. Patients who have compartment syndrome have 84.5 fold risk of mortality compared to those patients without compartment syndrome. Every day which passes from time of injury to admission predispose patients to develop pneumonia by 0.42 times. Incidence of electrical burns remain to be high in the Philippines due to the country's rapid rate of industrialization. Preventive measures such as use of proper protective equipment and public health campaigns should be done to reduce the incidence of electrical burns.